Augmented reality, virtual reality, and computer graphics. third International Conference, AVR 2016, Lecce, Italy, June 15-18, 2016. Proceedings /: third International Conference, AVR 2016, Lecce, Italy, June 15-18, 2016. Proceedings. Part II : (2016) - Unknown
No abstract available